2017
DOI: 10.1155/2017/5021902
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Lifestyle Interventions for Treating Overweight and Obesity in Children and Adolescents: A Systematic Review and Meta-Analyses

Abstract: Background Treatment of childhood obesity is important in preventing development of obesity-related diseases later in life. This systematic review evaluates the effect of multicomponent lifestyle interventions for children and adolescents from 2 to 18 years. Methods and Results We performed systematic searches in nine databases. Thirty-nine studies met the criteria for meta-analyses. We found a significant difference in body mass index (BMI) after 6 months (MD −0.99 (95% CI −1.36 to −0.61)), 12 months (MD −0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 96 publications
1
67
0
Order By: Relevance
“…Various reports and expert panels typically suggest BMI z-score reductions at benchmarks of 0.25, 0.20, and 0.15 as clinically signi cant and as associated with improvements in cardiometablic pro le [22,78]. While other reviews offer differing interpretations of clinically relevant BMI z-score improvements (e.g., 0.12-0.16) [79]. Notably, arresting gain in excess BMI also likely constitutes a clinically important bene t for many children [76,78,80].…”
Section: Discussionmentioning
confidence: 99%
“…Various reports and expert panels typically suggest BMI z-score reductions at benchmarks of 0.25, 0.20, and 0.15 as clinically signi cant and as associated with improvements in cardiometablic pro le [22,78]. While other reviews offer differing interpretations of clinically relevant BMI z-score improvements (e.g., 0.12-0.16) [79]. Notably, arresting gain in excess BMI also likely constitutes a clinically important bene t for many children [76,78,80].…”
Section: Discussionmentioning
confidence: 99%
“…Group‐based treatment of childhood obesity may be more effective than individual approaches. A review suggested an enhanced effect of group interventions at 6‐month follow‐up, but there was no evidence for longer‐term effects . Although health services in the primary care setting are important for detecting and managing obesity and its complications, there is little evidence of effective primary care interventions .…”
Section: Introductionmentioning
confidence: 99%
“…2 Modest improvements in weight and weight-related outcomes have been reported often in response to multicomponent lifestyle interventions for treating childhood obesity. 3,4 A review of lifestyle interventions indicated that immediate post-intervention improvements in children's weight status were not sustained over long term. 3 Additionally, changes in health outcomes other than weight status as cardiometabolic risk factors have been reported infrequently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While prevention of obesity is important, so too is the provision of effective clinical care to those who are affected. Treatment of children with obesity requires multi-disciplinary, multicomponent interventions, with early parental/carer involvement to encourage family-wide changes [2][3][4]. The optimal model of care for children with obesity, from an economic and health viewpoint, is an evidence-based staged approach to management, where primary, secondary and tertiary services are involved depending on severity and the response to treatment [5].…”
Section: Introductionmentioning
confidence: 99%